Relationship between Calcification on Mammography and Human Epidermal Growth Factor Receptor 2 (HER-2) Expression in Breast Carcinoma - Zulfadli Zulfadli; Hari Soekersi; Raden Yohana; Birgitta M. Dewayani (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Breast carcinoma shows over-expression of Human Epidermal Growth Factor Receptor 2 (HER-2) in 18 to 20% of the cases. This type of cancer is very progressive and has a poor prognosis. This study aimed to determine the association between the calcification on mammography with HER-2 expression in breast carcinoma as a marker of breast carcinoma aggressiveness.Methods: This was an analytic observational study with a case-control design. Patients with breast carcinoma at the Department of Radiology and Department of Anatomical Pathology of Dr. Hasan Sadikin General Hospital Bandung from July–September 2019 were enrolled in this study. Samples were consecutively collected. The association of calcification on mammography and HER2 expression was analyzed using the Chi-square test.Result: In total, 40 patients were included, consisting of 20 individuals with HER-2 positive and 20 individuals with HER-2 negative. The youngest was 40 years old and the oldest was 73 years old. Statistical test results showed that there was a significant association between calcifications in mammography and HER-2 expression (p-value = 0.0001, OR 13.22; 95% CI 2.7–62.6).Conclusions: There is a significant association between calcification on mammography and HER-2 expression in breast carcinoma, suggesting that positive calcification mammography was 13.22 times higher in patients with HER-2 positive compared to patients with negative calcifications.